Health and Safety at Work in the Transport Industry (TRANS-12): Factorial Structure, Reliability and Validity - Asens-Serra, Jordi; Serrano-Fernández, María-José; Boada-Cuerva, Maria; Boada-Grau, Joan; Macip-Simó, Sergi; Vigil-Colet, Andreu (Anales de Psicología / Annals of Psychology, 2018)
Background: This study sets out the psychometric properties of the TRANS-18 scale and of a shorter version, the TRANS-12, both designed to detect safe behaviors (personal and vehicle-related) and psychophysiological disorders among professional drivers. Method: The investigation was divided into Study 1, into the factorial structure, reliability and validity of the TRANS-18, and Study 2, looking into the same aspects of the TRANS-12. The participants in both studies were resident in Spain. 272 professional drivers took part in Study 1, while Study 2 had 326 participants. Results: A confirmatory factor analysis was carried out for both studies. The results for Study 1 confirm an internal structure of three factors related to psychophysiological disorders and personal and vehicle-related safety behaviors, but the original TRANS-18 is discarded because it does not fit the model. With regard to Study 2, the results show a good fit of the three-factor model, appropriate reliability and evidence of validity. Conclusions: We conclude by considering the suitability of the psychometric properties of the TRANS-12 and its utility for identifying safe behaviors in work in the transport industry.